2022
DOI: 10.3389/fendo.2022.932516
|View full text |Cite
|
Sign up to set email alerts
|

Alpha cell dysfunction in type 1 diabetes is independent of a senescence program

Abstract: Type 1 Diabetes (T1D) is caused by insulin deficiency, due to progressive autoimmune destruction of pancreatic β cells. Glucagon-secreting α cells become dysfunctional in T1D and contribute to pathophysiology, however, the mechanisms involved are unclear. While the majority of β cells are destroyed in T1D, some β cells escape this fate and become senescent but whether α cell dysfunction involves a senescence program has not been explored. Here we addressed the question of whether α cells become senescent durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…p16 Ink4a expression was already quite high even in the youngest pediatric donors examined in that study (aged 12-14), consistent with the age-related β-cell maturation and cell cycle exit. Replicating this observation in a culture model, DNA damage-induced senescence in islets from healthy donors leads to stable activation of p21 Cip1 but not p16 Ink4a ( 1 , 34 , 35 ) and more recently p21 Cip1 expression was confirmed in β-cells in this model ( 36 ). Additional evidence for distinctions between p21 Cip1 and p16 Ink4a in senescent β-cells was recently shown with the INK-ATTAC mouse model, which revealed that ablation of p16 Ink4a -expressing β-cells left a remaining senescent β-cell population expressing SASP factor genes ( 96 ).…”
Section: Molecular Mechanisms Of β-Cell Senescencementioning
confidence: 57%
See 2 more Smart Citations
“…p16 Ink4a expression was already quite high even in the youngest pediatric donors examined in that study (aged 12-14), consistent with the age-related β-cell maturation and cell cycle exit. Replicating this observation in a culture model, DNA damage-induced senescence in islets from healthy donors leads to stable activation of p21 Cip1 but not p16 Ink4a ( 1 , 34 , 35 ) and more recently p21 Cip1 expression was confirmed in β-cells in this model ( 36 ). Additional evidence for distinctions between p21 Cip1 and p16 Ink4a in senescent β-cells was recently shown with the INK-ATTAC mouse model, which revealed that ablation of p16 Ink4a -expressing β-cells left a remaining senescent β-cell population expressing SASP factor genes ( 96 ).…”
Section: Molecular Mechanisms Of β-Cell Senescencementioning
confidence: 57%
“…Conditioned media transfer experiments show that SASP factors secreted by β-cells are capable of triggering phenotypic changes in naïve recipient cells ( 1 3 , 35 ). Moreover, induction of SASP in human islets in culture leads to altered glucagon secretion from α-cells, suggesting that SASP from β-cells can affect α-cell function ( 36 ). BET inhibitor iBET-762, which reduces SASP, can partially rescue the glucagon secretion phenotype ( 36 ), lending further evidence implicating SASP in impaired α-cell function.…”
Section: Impact Of Senescence On β-Cell On Islet Function and Microen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry was performed as previously described [ 18 ]. Formalin fixed paraffin embedded pancreas tissue sections from 6-, 14-, and 17-week-old euglycemic NOD/ShiLtJ female mice (gift from A. Bhushan, UCSF) were rehydrated with xylene–ethanol washes, and antigen retrieval was performed with citrate buffer pH 6.0 (Vector Labs, Newark, NJ, USA) in a lab-grade pressure cooker (BioSB Tinto Retrieval system).…”
Section: Methodsmentioning
confidence: 99%
“…NIT-1 beta cells respond similarly to primary NOD mouse islet cells to inflammatory stimuli such as cytokines [ 17 ] and have been used extensively in the field to model molecular mechanisms of beta cell stress in T1D. Although these cells are transformed with Simian Virus 40 large T antigen, following sub-lethal DNA double-strand break damage, they undergo a growth arrest, activate a canonical DNA damage response, and stably upregulate p21 [ 16 ], recapitulating features of senescent primary beta cells in NOD mice [ 8 ] and human islet beta cells in a DNA damage-induced senescence model [ 18 ]. Senescent NIT-1 cells also produce a SASP involving insulin-like growth factor binding protein 3 (Igfbp3) and plasminogen activator inhibitor (Pai1) [ 16 ], two factors in common with the SASP of primary NOD beta cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%